2001
DOI: 10.1101/gad.852101
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles for the yeast SUB2/yUAP56 gene in splicing

Abstract: The UAP56 gene has been shown to be required for prespliceosome assembly in mammals. We report here the isolation of the Schizosaccharomyces pombe ortholog of this gene by heterologous complementation of a combined PRP40HA 3 /nam8⌬ defect in budding yeast. The Saccharomyces cerevisiae ortholog, YDL084w/SUB2, is also able to suppress this defect. We show that SUB2 is involved in splicing in vivo as well as in vitro. Sub2 defective extracts form a stalled intermediate that contains U2snRNP and can be chased into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
119
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 23 publications
(31 reference statements)
6
119
0
Order By: Relevance
“…splicing factors by Yra1p+ Notably, mutations in a region of Yra1p that has previously been shown to mediate a direct interaction with Sub2p (Sträßer & Hurt, 2001) largely abolish the ability of the protein to regulate its own expression (Fig+ 5)+ Sub2p has been shown to promote spliceosome formation (Kistler & Guthrie, 2001;Libri et al+, 2001;Zhang & Green, 2001) and bears the hallmarks of ATP-dependent "resolvases" (Staley & Guthrie, 1998)+ Thus Sub2p might possess an unwinding activity that could be used to resolve an RNA structure unfavorable for YRA1 splicing+ Alternatively, Sub2p might promote splicing by displacing an inhibitory factor from the YRA1 pre-mRNA+ In the light of recent data from our laboratory, we consider the latter possibility more likely (Kistler & Guthrie, 2001)+ In that study, it was shown that a deletion of Mud2p, the yeast homolog of vertebrate U2AF65, bypasses the requirement for Sub2p+ Because Mud2p interacts with the branchpoint region at an early stage of pre-mRNA recognition, these data can be best explained by a requirement of Sub2p to remove Mud2p from the premRNA and to allow spliceosome formation to proceed+ In our working model (Fig+ 7), YRA1 autoregulation is achieved in part by direct binding of Yra1p to Sub2p, thereby affecting Sub2p's ability to remove an inhibitory factor from the pre-mRNA+ Further experiments are required to elucidate the cis-and trans-acting elements involved in Yra1p regulation+ For example, it will be interesting to test whether mutations in Sub2p, Mud2p, or other factors involved in recognition of the branchpoint and/or 39 splice site affect YRA1 regulation+ Our observation that intronless yra1-F223S cannot support growth suggests that there may be additional levels of intron-dependent regulation (Fig+ 6C)+ This is reminiscent of L30 expression, which is regulated by feedback inhibition of splicing as well as of translation of its own mRNA (Dabeva & Warner, 1993)+ Interestingly, both forms of L30 autoregulation depend on very similar cis-acting sequences in the RNA+ Because overexpression of Yra1p causes nuclear accumulation of poly(A) ϩ mRNA, it seems possible that, at physiological concentrations, Yra1p modulates the nuclear export of specific mRNAs through nuclear retention+ Such an activity could conceivably serve as an additional mechanism for Yra1p autoregulation by inhibiting the export of YRA1 mRNA at elevated Yra1p levels (Fig+ 7)+ Alternatively, Yra1p might also affect the transcription of its own gene+ Circumstantial evidence in support of this hypothesis comes from the fact that its mammalian homolog has previously been identified as a transcriptional coactivator (Bruhn et al+, 1997;Virbasius et al+, 1999)+ More recently, Yra1p was found to be associated with a protein complex involved in transcription elongation in yeast )+ Finally, in light of accumulating evidence that the processes of transcription, pre-mRNA splicing, and mRNA export are coordinated (Bentley, 2002), it seems possible that the expression of Yra1p is achieved by a combination of mechanisms that act at each of these steps of gene expression (see below)+ The tight control of Yra1p levels is required for efficient mRNA export and cell viability…”
Section: Mechanism Of Yra1 Autoregulationmentioning
confidence: 99%
“…splicing factors by Yra1p+ Notably, mutations in a region of Yra1p that has previously been shown to mediate a direct interaction with Sub2p (Sträßer & Hurt, 2001) largely abolish the ability of the protein to regulate its own expression (Fig+ 5)+ Sub2p has been shown to promote spliceosome formation (Kistler & Guthrie, 2001;Libri et al+, 2001;Zhang & Green, 2001) and bears the hallmarks of ATP-dependent "resolvases" (Staley & Guthrie, 1998)+ Thus Sub2p might possess an unwinding activity that could be used to resolve an RNA structure unfavorable for YRA1 splicing+ Alternatively, Sub2p might promote splicing by displacing an inhibitory factor from the YRA1 pre-mRNA+ In the light of recent data from our laboratory, we consider the latter possibility more likely (Kistler & Guthrie, 2001)+ In that study, it was shown that a deletion of Mud2p, the yeast homolog of vertebrate U2AF65, bypasses the requirement for Sub2p+ Because Mud2p interacts with the branchpoint region at an early stage of pre-mRNA recognition, these data can be best explained by a requirement of Sub2p to remove Mud2p from the premRNA and to allow spliceosome formation to proceed+ In our working model (Fig+ 7), YRA1 autoregulation is achieved in part by direct binding of Yra1p to Sub2p, thereby affecting Sub2p's ability to remove an inhibitory factor from the pre-mRNA+ Further experiments are required to elucidate the cis-and trans-acting elements involved in Yra1p regulation+ For example, it will be interesting to test whether mutations in Sub2p, Mud2p, or other factors involved in recognition of the branchpoint and/or 39 splice site affect YRA1 regulation+ Our observation that intronless yra1-F223S cannot support growth suggests that there may be additional levels of intron-dependent regulation (Fig+ 6C)+ This is reminiscent of L30 expression, which is regulated by feedback inhibition of splicing as well as of translation of its own mRNA (Dabeva & Warner, 1993)+ Interestingly, both forms of L30 autoregulation depend on very similar cis-acting sequences in the RNA+ Because overexpression of Yra1p causes nuclear accumulation of poly(A) ϩ mRNA, it seems possible that, at physiological concentrations, Yra1p modulates the nuclear export of specific mRNAs through nuclear retention+ Such an activity could conceivably serve as an additional mechanism for Yra1p autoregulation by inhibiting the export of YRA1 mRNA at elevated Yra1p levels (Fig+ 7)+ Alternatively, Yra1p might also affect the transcription of its own gene+ Circumstantial evidence in support of this hypothesis comes from the fact that its mammalian homolog has previously been identified as a transcriptional coactivator (Bruhn et al+, 1997;Virbasius et al+, 1999)+ More recently, Yra1p was found to be associated with a protein complex involved in transcription elongation in yeast )+ Finally, in light of accumulating evidence that the processes of transcription, pre-mRNA splicing, and mRNA export are coordinated (Bentley, 2002), it seems possible that the expression of Yra1p is achieved by a combination of mechanisms that act at each of these steps of gene expression (see below)+ The tight control of Yra1p levels is required for efficient mRNA export and cell viability…”
Section: Mechanism Of Yra1 Autoregulationmentioning
confidence: 99%
“…Pre-mRNA splicing requires both small nuclear ribonucleoprotein particles (snRNPs) and non-snRNP protein factors+ Genetic and biochemical studies have uncovered most of the essential components for catalyzing the splicing reaction within the spliceosome (reviewed by Kramer, 1996;Burge et al+, 1999)+ Although the two transesterifications are likely to be catalyzed by the RNA core established in the spliceosome (reviewed by Nilsen, 1998), recognition of correct splice sites and formation of the catalytic core require multiple components assembled on pre-mRNA in an orderly fashion+ Analysis of splicing complexes shows that spliceosome assembly is initiated by U1 snRNP base pairing with the 59 splice site in an ATP-independent manner followed by ATP-dependent U2 snRNP recognition of the branchpoint sequence+ The established prespliceosome is then converted to mature spliceosome by the joining of the U4/5/6 tri-snRNP (reviewed by Burge et al+, 1999)+ Many initial contacts of critical splicing signals by snRNPs and non-snRNP factors likely take place much earlier, before the formation of stable complexes at distinct stages+ For example, it was recently shown that U2 snRNP establishes a functional contact with the U1-pre-mRNA complex in the absence of ATP (Das et al+, 2000) and that U4/5/6 tri-snRNP contacts the 59 splice site in an ATP-dependent manner prior to the base pairing interaction between U2 and the branchpoint sequence (Maroney et al+, 2000)+ A central question regarding efficient and accurate intron removal is how the 59 and 39 splice sites are recognized during the splicing reaction+ Selection of the 59 splice site appears to be determined initially by base pairing between U1 snRNP and the consensus intronic sequence at the 59 splice site+ This basepairing interaction is aided by the cap-binding protein CBP80 as well as a number of U1-associated proteins in budding yeast (Puig et al+, 1999;Zhang & Rosbash, 1999)+ The consensus 59 sequence is later proofread by base pairing with U6 (Kandels- Lewis & Séraphin, 1993;Lesser & Guthrie, 1993)+ The sequential recognition of the 59 splice site by U1 and subsequently by U6 is mediated by the RNA helicase Prp28 (Staley & Guthrie, 1999;Chen et al+, 2001)+ Selection of the 39 splice site appears to involve a more complex strategy+ In both yeast and humans, BBP/SF1 binds to the branchpoint sequence and Mud2/U2AF 65 interacts with the polypyrimidine tract (Abovich & Rosbash, 1997;Berglund et al+, 1997)+ These sequence-specific protein-RNA interactions set the stage for the RNA helicase Sub2/UAP56 to mediate U2 base pairing with the branchpoint sequence (Berglund et al+, 1998;Kistler & Guthrie, 2001;Libri et al+, 2001;…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was reported that splicingdependent recruitment of REF/Aly requires the putative RNA helicase UAP56 (Luo et al 2001;Strasser and Hurt 2001), which has also been implicated in early spliceosome assembly (Kistler and Guthrie 2001;Libri et al 2001;Zhang and Green 2001). In yeast, it has been proposed that Sub2p (the UAP56 ortholog) serves to recruit Yra1p (the REF/Aly ortholog) to mRNAs but then must dissociate to allow interaction between Yra1p and Mex67p (the TAP ortholog; Strasser and Hurt 2001).…”
Section: Insights Into Ejc Structure and Assemblymentioning
confidence: 99%
“…REF/Aly and TAP:p15 are mRNA export factors, and their association with the EJC can facilitate nuclear export of spliced RNAs (Luo and Reed 1999;Zhou et al 2000;Le Hir et al 2001a). REF/Aly and TAP:p15 are recruited to spliced mRNAs through physical interactions with UAP56 (Luo et al 2001;Strasser and Hurt 2001), a putative RNA helicase also implicated as a splicing factor required for early spliceosome assembly (Kistler and Guthrie 2001;Libri et al 2001;Zhang and Green 2001). Upf2 and Upf3 are factors required for nonsense-mediated mRNA decay (NMD), the process by which cells eliminate mRNAs containing incomplete open reading frames.…”
mentioning
confidence: 99%